JCMT 2021
DOI: 10.20517/2394-4722.2021.08
|View full text |Cite
|
Sign up to set email alerts
|

Leelamine suppresses cMyc expression in prostate cancer cells in vitro and inhibits prostate carcinogenesis in vivo

Abstract: Aim: Leelamine (LLM) inhibits the growth of human prostate cancer cells but the underlying mechanism is not fully understood. The present study was undertaken to determine the effect of LLM on cMyc, which is overexpressed in a subset of human prostate cancers. Methods:The effect of LLM on cMyc expression and activity was determined by western blotting/confocal microscopy and luciferase reporter assay, respectively. A transgenic mouse model of prostate cancer (Hi-Myc) was used to determine the chemopreventive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…In this study, our goal was to investigate the diverse molecular mechanisms through which LEE could target the invasion and migration of breast cancer cells. We selected LEE as it has been previously reported to exhibit anticancer efficacy in some studies but its impact on the CXCR7/4 axis and EMT process has not been reported [ 3 , 4 , 5 , 6 , 7 , 8 ]. Thus, our study mainly examined the impact of LEE on the regulation of the EMT process by targeting the CXCR7/4 signaling axis in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, our goal was to investigate the diverse molecular mechanisms through which LEE could target the invasion and migration of breast cancer cells. We selected LEE as it has been previously reported to exhibit anticancer efficacy in some studies but its impact on the CXCR7/4 axis and EMT process has not been reported [ 3 , 4 , 5 , 6 , 7 , 8 ]. Thus, our study mainly examined the impact of LEE on the regulation of the EMT process by targeting the CXCR7/4 signaling axis in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer cells, LEE caused inhibition of fatty acid synthesis mediated by sterol regulatory element-binding protein 1 (SREBP1) [ 7 ]. In another study, it was reported that the anticancer effects of LEE in the prostate cancer were mediated through downregulation of cMyc in vitro and in vivo [ 8 ]. In the present study, the anticancer activity of LEE in human breast cancer cells was explored.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with former study (16), LNCap cells and primary prostate epithelial cells were be used in this study to investigate NF-κB regulates AR expression and EMT in prostatitis and PCa. Compared with DU145 cells and PC3 cells, LNCap cells showed more androgen-sensitive and have remarkable epithelial properties, which widely used in EMT research (17). What's more, this is the first time to apply primary prostate epithelial cells, which sampled from patients who were suspected of PCa and had histological prostatitis (HP) confirmed by pathological biopsy, in prostatitis-PCa-EMT research.…”
Section: Original Articlementioning
confidence: 99%